2016
DOI: 10.1016/j.bbi.2015.09.006
|View full text |Cite
|
Sign up to set email alerts
|

IL-1 receptor signaling in the basolateral amygdala modulates binge-like ethanol consumption in male C57BL/6J mice

Abstract: Proinflammatory cytokines have been implicated in alcohol-induced neurodegeneration, but the role of the neuroimmune system in alcohol related behaviors has only recently come to the forefront. Herein, the effects of binge-like drinking on IL-1β mRNA and immunoreactivity within the amygdala were measured following the “drinking in the dark” (DID) paradigm, a model of binge-like ethanol drinking in C57BL/6J mice. Moreover, the role of IL-1 receptor signaling in the amygdala on ethanol consumption was assessed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
63
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(79 citation statements)
references
References 61 publications
8
63
1
4
Order By: Relevance
“…Adjacent sections have previously been analyzed for IL-1β (Marshall et al 2016a). Briefly, sections were rinsed in 0.1M PBS before endogenous peroxidases were quenched with 0.6% H 2 O 2 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Adjacent sections have previously been analyzed for IL-1β (Marshall et al 2016a). Briefly, sections were rinsed in 0.1M PBS before endogenous peroxidases were quenched with 0.6% H 2 O 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Determining the neuroimmune response following binge-like drinking in the absence of dependence will tease apart the acute contributions of binge ethanol consumption on neuroimmune responses from those associated with neurodegeneration or other comorbidities associated with ethanol misuse. Recently, it has been shown that binge-like ethanol consumption during the DID paradigm is sufficient to elicit an increase in IL-1β in the amygdala indicating that even acute excessive ethanol consumption can cause dysregulation of the neuroimmune system (Marshall et al 2016a). However, the influence of alcohol on anti-inflammatory cytokines, like IL-10 and IL-4, have yet to be explored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because both neurons and astrocytes express IL-1 receptors, it cannot be determined if the electrophysiological consequences are driven by glial dependent or independent mechanisms, a caveat that is worth considering for many of the studies examined here. Regardless, inhibition of IL-1 signaling in the basolateral amygdala via local infusions of IL-1 receptor antagonist reduced acquisition of alcohol, suggesting that cytokine expression in the amygdala could modulate the reinforcing effects of alcohol (Marshall et al, 2016).…”
Section: Alcohol Glia and Neuroimmune Signalingmentioning
confidence: 99%
“…However, reducing endotoxin release with antibiotics, probiotics, and drugs resulted in a loss of the stress hormone response, suggesting stress‐induced changes in blood endotoxin contribute to stress hormone responses (Ait‐Belgnaoui et al., 2012). Innate immune signaling cytokines also alter EtOH consumption (Marshall et al., 2016, 2017), and the cytokine receptors IL1R1 and TNFR1 contribute to stress‐induced EtOH consumption (Karlsson et al., 2017), suggesting the neuroimmune system may contribute to addiction. Cytokines also enhance stressful emotional states following alcohol withdrawal (Breese et al., 2008).…”
mentioning
confidence: 99%